Risk behaviour and HIV prevalence among men who have sex with men in a multiethnic society: a venue-based study in Kuala Lumpur, Malaysia - Kanter, J.; Koh, C.; Razali, K.; Tai, R.; Izenberg, J.; Rajan, L.; Van Griensven, F.; Kamarulzaman, Adeeba (SAGE Publications, 2011)
This research aimed to determine HIV prevalence, risk behaviour and knowledge of transmission methods among men who have sex with men (MSM) in Kuala Lumpur, Malaysia. Venue-day-time sampling (VDTS) was applied to identify venues where men congregate to solicit sex from other men. Participants recruited from clubs, massage parlours, saunas and one park self-completed a computerized behavioural questionnaire, were administered an oral rapid HIV test and given the opportunity to return later to receive full counselling and learn their HIV status. A total of 517 men were enrolled into the study. The majority were Malays (47.0) and Chinese (43.7). Twenty tested HIV positive (3.9). Significant predictors of HIV infection included having unprotected anal sex with a casual partner (44.9 of participants, odds ratio OR = 2.99; 95% confidence interval CI 1.13-7.90; P = 0.027), having unprotected receptive anal sex (27.9%, OR = 2.71; 95% CI 1.10-6.54; P = 0.030) and having group sex (33.3%, OR = 3.95; 95% CI 1.55-10.09; P = 0.004). One in five participants (20.1% and 19.5%) did not believe that HIV could be transmitted through insertive or receptive anal sex, respectively. Risk behaviour is high and knowledge of HIV transmission methods was low among MSM in Kuala Lumpur. Future prevention efforts should focus on providing risk reduction education to this community.